Process optimization and identification of antioxidant peptides from enzymatic hydrolysate of bovine bone extract, a potential source in cultured meat - Begum, Nabila; Khan, Qudrat Ullah; Al-Dalali, Sam; Lu, Daoqiang; Yang, Fang; Li, Jie; Wu, Di; Li, Riwang; Wang, Jun; Liu, Dahai; Song, Huanlu (Frontiers in Sustainable Food Systems, 2024)
Bone protein is a significant secondary product of the meat industry, comprising a substantial quantity of protein. These proteins could be broken down through enzymatic hydrolysis to generate antioxidant peptides. This study aimed to produce antioxidant peptides from bovine bone extract by enzymatic hydrolysis utilizing Flavourzyme and Protamex by optimizing enzyme amounts and time using the Box–Behnken design. The final optimized conditions obtained through the model were as follows: The amount of Flavourzyme was 1,100 U, the amount of Protamex was 2,814 U, and the time was 3.77 (h). Bovine bone extract hydrolysate (BBEH) was purified stepwise using ultrafiltration membranes with molecular cutoffs of 5, 3, and 1 kDa. To assess the antioxidant capacity of the fractions, several methods were used, including radical scavenging activity “1,1-diphenyl-2-picrylhydrazyl (DPPH),” “2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS),” metal chelating activity (MCA), reducing power (RP), and thiobarbituric acid assay (TBA). The results indicated that the ultrafiltration fraction with a molecular weight of less than 1 kDa showed significant antioxidant activity, with 48, 42, and 50% inhibition rates for DPPH, ABTS, and metal chelating, respectively. Using size exclusion chromatography, the fraction with a molecular weight less than 1 kDa was further separated into five sub-fractions: Frac-I, Frac-II, Frac-III, Frac-IV, and Frac-V. Sub-Frac-III, which exhibits significant DPPH radical scavenging activity (55%) and a reducing power of 0.8 at 700 nm, was separated into six sub-sub-fractions using reversed-phase HPLC (RP-HPLC) based on molecular weight and hydrophobicity. The sub-sub-fraction with the highest value for DPPH radical scavenging activity was sub-Fra-III-6, which exhibited approximately 69.45% activity. The sub-Fra-III-6 was analyzed using LC–MS/MS, which identified two specific peptides: Ala-Pro-Phe with a mass of 333.12 Da and Asp-His-Val with a mass of 369.14 Da. These two peptides are likely the primary peptides that might have a crucial role in antioxidant capacity. It can be concluded that BBEH is a valuable source of natural antioxidants and has the potential to serve as a viable resource in the cultured meat industry.